Analysis of the Needs for Audio-Visual Media Based on the Canva Application in Social Studies Learning for Grade VI Elementary Schools in Sumberrejo District, Bojonegoro Regency - Sumunik Sumunik; Herry Widyastono; Eka Budhi Santosa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This study aims to describe the needs of teachers regarding audio-visual media based on the Canva application in social studies learning for class VI SD with the sub-theme of Defending Independence. This type of descriptive analytical research is in the form of a survey. Respondents of all social studies teachers at grade VI in the Sumberrejo District were 40 teachers. Data was collected by questionnaire using google form, analyzed by descriptive statistics, especially percentages in graphical form. The results of the study show the experience of teachers using electronic media mostly uses the zoom platform. The teacher's assessment of students' learning motivation when participating in online learning is mostly low. Factors causing low student learning motivation because teachers only use PowerPoint media during online learning. The information technology learning media used by the teacher to be able to increase student motivation according to the teacher is powerpoint accompanied by audio-visual. In general, teachers are not familiar with the Canva application. Interesting audio-visual media content developed with the Canva application is narration with powerpoint and audio-visual, especially YouTube. In general, teachers' difficulties in developing audio-visual media based on the Canva application are limited visual references (images) and audio-visual, especially YouTube. Therefore it is necessary to conduct a study on the development of audio-visual media based on the Canva application in social studies learning for class VI elementary schools for teachers in the study location.